Evidence of penalty kicks in the fifa world cup 2022 - Hanif Nugroho; Hedi Ardiyanto Hermawan; muhad fatoni; Agam Akhmad Syaukhani (Jorpres (Jurnal Olahraga Prestasi), 2026)
Penalty kicks in soccer become crucial moments that determine the outcome of the match. This research aims to analyze penalty kicks in terms of dominant foot and direction. Data were collected through video analysis of soccer players' penalty kicks in the 2022 FIFA World Cup matches via the official FIFA website. This study involved 5 videos of penalty shootout matches with a total of 41 kicks performed by professional players. Based on the analysis results, it was found that in the penalty shootout of the 2022 World Cup, 80.49% of players took the kick using their dominant right foot, and 19.51% used their dominant left foot. Regarding the target direction chosen by players, it was observed that players with dominant right foot more often aimed the ball towards the bottom left, while players with dominant left foot more frequently aimed towards the bottom middle. When considering the success rate of kicks resulting in goals, kicks with dominant right foot had a higher success rate when aimed towards the top middle and bottom middle, whereas kicks with dominant left foot had a higher success rate when aimed towards the bottom middle and bottom left. The research results indicate that dominant foot and target direction are contributing factors to the success of penalty kicks.